SCHOOL BASED MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATION IN THE GLOBALIZATION ERA - Rahmi, Elvi; Hafizh, Muhammad; M, Amril Huda; Wahyuni, Sri Intan; Elfira, Ninil; Ahda, Muhammad Yazid (El-Rusyd, 2024)
The era of globalization demands changes in various aspects of life, including in the world of education. One of the efforts to improve the quality of education in the midst of global challenges is to implement School-Based Management. The purpose of this research is to find out how the implementation of school-based management can improve the quality of education in schools. This research uses a descriptive qualitative method with data collection techniques through observation, interviews and documentation studies. The results showed that 1) school-based management in improving service quality provides educational services that are responsive, efficient, and relevant to students' needs, 2) school-based management in improving curriculum quality produces learning that is relevant, innovative, and oriented to the development of students' competencies as a whole, while 3) school-based management in managing and developing facilities and infrastructure can create a physical environment that supports the learning process, the implementation of school-based management has a positive impact on improving the quality of education, especially in the field of education. Thus, school-based management is an effective strategy to improve the quality of education in the era of globalization, where the active role of all stakeholders is very important to achieve the goals of quality education and global competitiveness.